Evidence for Interhemispheric Mercury Exchange in the Pacific Ocean Upper Troposphere. Issue 10 (24th May 2022) - Koenig, Alkuin M.; Sonke, Jeroen E.; Magand, Olivier; Andrade, Marcos; Moreno, Isabel; Velarde, Fernando; Forno, Ricardo; Gutierrez, René; Blacutt, Luis; Laj, Paolo; Ginot, Patrick; Bieser, Johannes; et al.
Abstract: Even though anthropogenic mercury (Hg) emissions to the atmosphere are ∼2.5 times higher in the Northern Hemisphere (NH) than in the Southern Hemisphere (SH), atmospheric Hg concentrations in the NH are only ∼1.5 times higher than in the SH. Global Hg models attribute this apparent discrepancy to large SH oceanic Hg emissions or to interhemispheric exchange of Hg through the atmosphere. However, no observational data set exists to serve as a benchmark to validate whether these coarse‐resolution models adequately represent the complex dynamics of interhemispheric Hg exchange. During the 2015–2016 El Niño, we observed at mount Chacaltaya in the tropical Andes a ∼50% increase in ambient Hg compared to the year before, coinciding with a shift in synoptic transport pathways. Using this event as a case study, we investigate the impact of interhemispheric exchange on atmospheric Hg in tropical South America. We use HYSPLIT to link Hg observations to long‐range transport and find that the observed Hg increase relates strongly to air masses from the tropical Pacific upper troposphere (UT), a region directly impacted by interhemispheric exchange. Inclusion of the modeled seasonality of interhemispheric air mass exchange strengthens this relationship significantly. We estimate that interhemispheric exchange drives Hg seasonality in the SH tropical Pacific UT, with strongly enhanced Hg between July and October. We validate this seasonality with previously published aircraft Hg observations. Our results suggest that the transport of NH‐influenced air masses to tropical South America via the Pacific UT occurs regularly but became more detectable at Chacaltaya in 2015–2016 because of a westward shift in air mass origin. Plain Language Summary: Human activities have released much more mercury, a toxic pollutant, into the Northern Hemisphere (NH) atmosphere than into the Southern Hemisphere (SH) atmosphere. Yet, the difference in mercury concentrations between the two hemispheres is not very large. Model studies attribute this unexpectedly low interhemispheric mercury difference to large emissions from SH oceans or to the exchange of airborne mercury between hemispheres. This interhemispheric mercury exchange is complex, however, and direct observational evidence is lacking. Here, we examine the strong increase in atmospheric mercury during the 2015–2016 El Niño at mount Chacaltaya in tropical South America. We examine and exclude potential SH sources for this increase, such as mercury emissions from wildfires or marine mercury emissions. Instead, we find that this mercury increase was likely caused by interhemispheric mercury exchange at high altitudes over the tropical Pacific Ocean, and the subsequent transport of mercury‐rich NH‐influenced air to tropical South America. We propose that Chacaltaya mercury observations could be used as a reference to test if current mathematical models can correctly predict interhemispheric mercury exchange. Key Points: We use the strong increase in atmospheric Hg at Chacaltaya mountain in tropical South America during the 2015–2016 El Niño for a case study In 2015–2016, air mass origin for Chacaltaya shifted westward, with greatly enhanced influence of the tropical Pacific upper troposphere (UT) Our results suggest that interhemispheric exchange in the tropical Pacific UT can bring Northern Hemisphere Hg to Chacaltaya